Love on the brain [large type] - Hazelwood, Ali (Center Point Large Print, 2022)
"Like an avenging, purple-haired Jedi bringing balance to the mansplained universe, Bee Königswasser lives by a simple code: What would Marie Curie do? If NASA offered her the lead on a neuroengineering project -- a literal dream come true after years scraping by on the crumbs of academia -- Marie would accept without hesitation. Duh. But the mother of modern physics never had to co-lead with Levi Ward. Sure, Levi is attractive in a tall, dark, and piercing-eyes kind of way. And sure, he caught her in his powerfully corded arms like a romance novel hero when she accidentally damseled in distress on her first day in the lab. But Levi made his feelings toward Bee very clear in grad school -- archenemies work best employed in their own galaxies far, far away. Now, her equipment is missing, the staff is ignoring her, and Bee finds her floundering career in somewhat of a pickle. Perhaps it's her occipital cortex playing tricks on her, but Bee could swear she can see Levi softening into an ally, backing her plays, seconding her ideas . . . devouring her with those eyes. And the possibilities have all her neurons firing. But when it comes time to actually make a move and put her heart on the line, there's only one question that matters: What will Bee Königswasser do?"--